ETIOTROPIC TREATMENT OF PNEUMONIA IN CHILDREN AT THE CURRENT STAGE - Kholmuradova Zilola Ergashevna (TADQIQOTLAR.UZ, 2025)
Etiotropic  treatment  of  any  disease  requires,  first  of  all,  knowledge  of  the pathogen and its sensitivity to antibiotics. Since, when meeting with an acute patient, the  doctor  cannot  delay  the  start  of  treatment  until  these  issues  are  clarified,  his empirical prescriptions should be carried out taking into account the likelihood of a particular pathogen and its sensitivity. Recent work has shown that the accuracy of the empirical choice of an antimicrobial drug can be very high (80-70%) when taking into account a number of obvious factors [1]. When addressing this issue, one should first of all take into account where the pneumonia  developed,  since  in  terms  of  etiology,  community-acquired  (“home-acquired”, community-acquired) pneumonia is fundamentally different from hospital-acquired pneumonia. The latter also includes cases of pneumonia developing in a child recently (less than 7 days) discharged from the hospital, as well as in a child receiving antibiotics at home. A special case is pneumonia in people with immunodeficiency, which is distinguished by both its particular severity with “common” pathogens and the participation of opportunistic flora. The Classification of Nonspecific Respiratory Diseases  in  Children  [2]  lists  the  probable  causative  of  pneumonia  of  these  main groups, however, to narrow the range of possible causative agents, it is advisable to supplement these data with two other characteristics - age and the nature of pneumonia.